THE EXPANSION OF EURASIAN CATTLE-BREEDING STEPPE TRIBES INTO NORTHERN BACTRIAN TERRITORIES - Karimova Dilafruz Obidjonovna (Galaxy International Interdisciplinary Research Journal, 2021)
It is known that the Bronze Age began with many innovations in human history. The interrelationships of the various tribes have intensified. During the Bronze Age, Northern Bactria became an area where cattle and peasant communities lived together. They are reflected in the findings from ancient cemeteries belonging to this period.